Tourism stock price and COVID-19: medium-term relationship with passenger transport, hotel, and tour operator subsectors - Carrillo-Hidalgo, Isabel; Pulido Fernández, Juan Ignacio; López-Sánchez, Yaiza; Durán-Román, Jose Luis (Routledge, 2023)
COVID-19 has had a devastating effect on tourism in Spain, one of the world’s biggest tourist destinations and also one of the first countries to face the consequences of the pandemic. Tourism stock prices showed high volatility at the beginning of the pandemic. However, we do not yet know whether this relationship has remained throughout the pandemic and the effect it has had on the main subsectors of tourism. Quantifying this relationship in the medium term makes it possible to predict the effect of the pandemic on the tourism sector stock market and to compare the impact on its different subsectors. A dynamic regression model has been developed to predict the stock price of the hotel, passenger transport, and tour operator subsectors in Spain, based on the evolution of COVID-19. Cumulative COVID-19 deaths have been confirmed to be a good predictor of abnormal stock price in the main tourism subsectors, affecting passenger transport more intensely than hotels or tour operators.
Keywords: COVID-19; España; Bolsa de valores; Turismo; Análisis de regresión; Spain; Abnormal stock price; Tourism stock price; Dynamic regression models; COVID-19